Pentingnya Pendidikan Kewarganegaraan bagi Suatu Negara pada Generasi Milenial Abad-21 - Wafa Khairunisa; Siska Damayanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The challenges of the globalization era for a country have an impact on the younger generation, the millennial generation of the 21st century. The crisis of ethics, morals, and character throughout the world has become a serious problem due to globalization. This research aims to develop civic science, especially at the level of the functions and benefits of civics for the civilization of a nation in the face of globalization. This is a qualitative research project using the literature review method (library research). The results of the study show that the importance of civic education for a country in the 21st century is overcoming the challenges of globalization, which are especially felt by the millennial generation, so that civic education becomes a pillar in building a nations identity.